PENGARUH KOMPETENSI SUMBER DAYA MANUSIA (SDM) DAN SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD) TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH DENGAN PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Satuan Kerja P - Desilia Tanzerina; M. Rasuli '; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to analyze the influence of knowledge, the effectiveness of the tax system, the service tax authorities to corporate taxpayers in meeting their financial obligations to the consciousness as a moderating variable. The population that will be used in this research are corporate taxpayers listed in KPP Madya Pekanbaru. Determination of the sample in this study using convinience sampling is a generic term that includes a variety breadth of respondent selection procedures. The sample in this study are corporate taxpayers listed in KPP Madya Pekanbaru who were represented by staff accounting, tax administration staff, the administrative staff of financial, accounting manager, manager of finance and accounting and tax supervisor totaling 100 people. The data analysis used is multiple regression (multiple regression) assisted with SPSS Windows Ver 20. The results of this study prove that knowledge, the effectiveness of the tax system, the service tax authorities significant effect on the obligation to pay taxes, awareness moderate the relationship between knowledge of the obligation to pay the tax in KPP Madya Pekanbaru. While awareness is not moderate the relationship between the effectiveness of the tax system and the tax authorities of the obligation to pay service tax at KPP Madya Pekanbaru.Keywords: Knowledge, Effectiveness, Tax, Awareness, and Paying Taxes.